Features of the Personality of an Exile on the Example of Vladimir Nabokov - Soghomonyan, Amalya (Bulletin of Yerevan University B: Philology, 2022)
Migration and exile have long been considered a meta-historical threat to writers, but the 20th century has become one of the defining (if not the most defining) features of the history of literature due to increasing migration. The issue that is most talked about in the context of immigrant literature is related to personal, national, cultural, and religious identity. The individual, appearing in a foreign culture, faces the problem of reinterpretation of identity and acquires a hybrid identity. The problem of identity is faced also by those who live next to migrants. In their own homeland, they look at their country through the eyes of a foreign and unknown immigrant writer. The explanation of the latter is very simple. We all live in the age of migration, where we are all potential migrants. Almost all immigrant writers face the problem of the collapse of ideas about their own "self". An émigré writer differs from an ordinary émigré: as he approaches the ideals that have inspired him throughout his life, it feels like going back home. The lack of a "home" concept is especially important for immigrant writers. They are often not accepted in their own country; after leaving the homeland, they become foreigners both at home and abroad. Sometimes writers manage to reconcile and even unite different cultures. Nabokov taught Russian literature in the United States, introducing American students to great Russian writers, although many compatriots have not yet forgiven Nabokov for emigrating. The illusion of Nabokov’s old creative "self", the disappearance of his once established literary identity, testifies to Nabokov’s desire to start all over again․ This is an opportunity that America offers to all immigrants.